Soluble urokinase plasminogen activator receptor predicts survival and hospitalization for heart failure in elective cardiac surgery. (3rd October 2022) - Koller, L; Steinacher, E; Hofer, F; Kazem, N; Laufer, G; Fleck, T; Wojta, J; Steinlechner, B; Richter, B; Hengstenberg, C; Niessner, A; Sulzgruber, P
Abstract: Aims: The study investigated the prognostic value of soluble urokinase plasminogen activator receptor (suPAR) patients undergoing cardiac surgery and calculated a simplified biomarker score comprising suPAR, N-terminal pro B-type natriuretic peptide (NT-proBNP) and age. Methods and results: Biomarkers were assessed in a cohort of 478 patients undergoing elective cardiac surgery. After a median follow-up of 4.2 years a total of 72 (15.1%) patients died. SuPAR, NT-proBNP and age were independent prognosticators of mortality in a multivariable Cox regression model after adjustment for EuroScoreII. We then calculated a simplified biomarker score comprising age, suPAR and NT-proBNP, which had a superior prognostic value compared to EuroScoreII (Harrel's C of 0.76 vs 0.72; P for difference = 0.02). Besides long-term mortality, the biomarker score had an excellent performance predicting one-year mortality and hospitalization due to heart failure. Conclusion: The biomarker suPAR and NT-proBNP were strongly and independently associated with mortality in patients undergoing cardiac surgery. A simplified biomarker score comprising only 3 variables (age, suPAR and NT-proBNP) performed better than the established EuroScoreII with respect to intermediate and long-term outcome as well as hospitalization due to heart failure. As such, integration of established and upcoming biomarkers in clinical practice may provide improved decision support in cardiac surgery. Funding Acknowledgement: Type of funding sources: None.